Precision cut tumor slices as an ex vivo model to assess myeloid biology and function in the tumor microenvironment - Honnér,Tindra; Nydemark,Julia (2025)
Precision cut tumor slices (PCTS) are used as an ex vivo tissue model to study the tumor microenvironment (TME), immune interactions and treatment-induced effects.They allow researchers to analyze individual patient responses to therapies, making them valuable for personalized medicine. In this study, PCTS generated from five biopsy samples collected from patients with head and neck cancer or esophageal cancer. After tissue slicing using a vibratome, the slices were treated with either lipopolysaccharide (LPS) as a positive control, the bispecific therapeutic antibodies ATOR-4066 and 4224, or left untreated. Flow cytometry was used to evaluate changes in immune cell populations and activation in response to these treatments. The study investigated the impact of slicing on cell viability, while also characterizing specific immune cell populations including CD4+-and CD8+ T cells, B cells and myeloid antigen presenting cells (APCs). Additionally, the tumor antigens CEACAM5 and EpCAM were analysed, along with immune activation markers CD86, PD-L1, CD69 and PD-1 to identify potential increase in activation and regulatory activity of the immune cells post treatment. Results showed a reduction of CD4+ T cells and myeloid APCs following slicing, suggesting a sensitivity to mechanical stress. No other consistent association between specific cell subset and slicing was observed. The expression levels of CEACAM5 and EpCAM were fairly low in all patient samples, implying a limited potential efficacy of the therapeutic agents ATOR-4066 and 4224. However, in two of the patient samples an increased expression of the PD-L1 marker indicated activation of B cells and myeloid APCs.
Keywords: Immunology; Ex vivo models; cancer; antibodies